Comparative Evaluation of a Single Intraoperative Dose of Intravenous Dexamethasone 8 mg and Betamethasone 8 mg on Post Caesarean Delivery Analgesia: A Randomised Controlled Trial - Vandana Koul; Robina Nazir; Rajesh Mahajan; Updesh Kumar; Ajay Gupta; Arti Gupta (Dr. Annil Mahajan, 2022)
Background: Administration of glucocorticoids prior to surgery has been shown to reduce the requirement for postoperative opioids and inpatient time, with minimal side effects. Objective: The efficacy of intravenous dexamethasone and betamethasone in parturients undergoing elective lower segment caesarean section under spinal anesthesia was evaluated in this randomized, double-blind research. Material & Methods: A total of 120 patients scheduled for a lower segment caesarean section under spinal anesthesia were randomly assigned to one of three groups (40 patients each): D (treatment: 8 mg IV dexamethasone), B (treatment: 8 mg IV betamethasone), and C (control: 2 ml of normal saline). The study medication was given intravenously shortly after spinal anesthesia. Results: The mean duration of sensory block (min) in group D and group B was 196.00 ± 10.63 and 193.73 ± 10.46, respectively, which was significantly higher than in group C, 180.38 ± 9.90. Time to the requirement of first rescue analgesia was also prolonged in group D (14.07 ± 2.10 h) and group B (12.23 ± 4.20 h) as compared to group C (5.66 ± 3.20 h). The duration of motor block, intraoperative and postoperative hemodynamic parameters were comparable. Conclusion: We conclude that administration of intravenous dexamethasone 8 mg and betamethasone 8 mg intravenously prolongs the duration of postoperative analgesia and sensory block in patients undergoing lower segment caesarean section under spinal anesthesia.